Applied Aqua-DST Training – Yangon, Myanmar - Win, Shelly; Myint, Aye Chan; Buisson, Marie-Charlotte; de Silva, Sanjiv; U, Phay Ko (2025)
The Applied Aqua-DST Training held in Yangon on 22–23 September 2025 successfully strengthened the capacity of Myanmar’s aquaculture stakeholders to use the full version of the Aquaculture Decision Support Tool (Aqua-DST), a multi-criteria suitability analysis platform designed to guide aquaculture planning across 170 townships in the Upper Ayeyarwady region. The event gathered 53 participants across two days, including government officers from the Department of Fisheries (DoF) and Department of Agriculture, members of the Myanmar Fishery Federation (MFF), university researchers, NGOs/CSOs, and private-sector representatives. A key milestone of the workshop was the official handover of the Aqua-DST Dashboard to the Department of Fisheries, underscoring national ownership and long-term integration of the tool into government-led aquaculture development. Participants received comprehensive training on the Aqua-DST Excel model, metadata structure, indicator weighting, township-level suitability mapping, and the use of Power BI for dashboard visualization. Through hands-on exercises, group work, debates, and scenario-based analysis, participants acquired practical skills for applying the tool to fishpond siting, feed supplier planning, hatchery expansion, and broader aquaculture investment decisions. Pre- and post-training assessments demonstrated substantial knowledge gains, with overall understanding rising from 42% to 87%. Participants highlighted the Aqua-DST as a cost-effective and relevant decision-support system, particularly for identifying priority areas for aquaculture expansion and minimizing risks associated with poor site selection. Participants also recommended expanding Aqua-DST to national scale and integrating it into university curricula and farmer-training platforms to support long-term uptake. The training concluded with strong interest in forming a national Aqua-DST working group to guide future refinements and ensure sustained application of the tool across Myanmar’s aquaculture landscape.